Human Rights and the New Zealand Government’s Treaty Obligations - Palmer, Geoffrey (Victoria University of Wellington Law Review, 1999)
The International Law Association established a New Zealand branch in Wellington in 1996. This article is an edited version of the speech made by Sir Geoffrey Palmer, on the occasion of the inaugural meeting of the Association in Auckland on 30 April 1998. The author discusses the place of international law in contemporary New Zealand society, especially following the Second World War. He then goes onto discuss international law and municipal law, arguing that there is a substantial degree of overlap between the two. Parliamentary involvement with treaties is also discussed, noting that recent Parliamentary scrutiny of treaties bolsters the argument in favour of courts giving enhanced weight to treaties to which New Zealand has acceded or ratified, even where there is no complementary local legislation. The article then goes onto discuss international law providing a framework for the delivery of human rights to individuals at a domestic level, including in New Zealand. The author expresses regret at New Zealand’s general failure to comply with international treaties, arguing that international environmental law and trade law were likely to present similar problems.